The Interaction of Klebsiella pneumoniae With Lipid Rafts-Associated Cholesterol Increases Macrophage-Mediated Phagocytosis Due to Down Regulation of the Capsule Polysaccharide - Ares, Miguel A.; Sansabas, Alejandro; Rodríguez-Valverde, Diana; Siqueiros-Cendón, Tania; Rascón-Cruz, Quintín; Rosales-Reyes, Roberto; Jarillo-Quijada, Ma. Dolores; Alcántar-Curiel, María D.; Cedillo, María L.; Torres, Javier; Girón, Jorge A.; De la Cruz, Miguel A. (Frontiers in Cellular and Infection Microbiology, 2019)
Klebsiella pneumoniae successfully colonizes host tissues by recognizing and interacting with cholesterol present on membrane-associated lipid rafts. In this study, we evaluated the role of cholesterol in the expression of capsule polysaccharide genes of K. pneumoniae and its implication in resistance to phagocytosis. Our data revealed that exogenous cholesterol added to K. pneumoniae increases macrophage-mediated phagocytosis. To explain this event, the expression of capsular galF, wzi and manC genes was determined in the presence of cholesterol. Down-regulation of these capsular genes occurred leading to increased susceptibility to phagocytosis by macrophages. In contrast, depletion of cholesterol from macrophage membranes led to enhanced expression of galF, wzi and manC genes and to capsule production resulting in resistance to macrophage-mediated phagocytosis. Cholesterol-mediated repression of capsular genes was dependent on the RcsA and H-NS global regulators. Finally, cholesterol also down-regulated the expression of LPS core oligosaccharides and OMPs. Our results suggest that cholesterol plays an important role for the host by reducing the anti-phagocytic properties of the K. pneumoniae capsule facilitating bacterial engulfment by macrophages during the bacteria-eukaryotic cell interaction mediated by lipid rafts.